2015
DOI: 10.1016/j.ophtha.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis in the National Veteran Population

Abstract: Purpose To describe the distribution of ocular sarcoidosis in the veteran population and to determine the association between ocular disease and all-cause mortality. Design Retrospective review. Methods The Veterans Health Administration National Patient Care Database information on medical diagnoses, date of diagnosis, age, race, gender, and Veterans Administration medical center station number for site-specific calculations for fiscal years 2010 through 2012 was collected. Mortality data were obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…Sarcoidosis is a systemic immune disorder with a characteristic accumulation of epithelioid granulomas in many organs, such as the lungs, kidney, skin and eyes [ 50 , 51 ]. Chronic sarcoidosis is disease activity lasting more than 2 years [ 52 , 53 ].…”
Section: Reviewmentioning
confidence: 99%
“…Sarcoidosis is a systemic immune disorder with a characteristic accumulation of epithelioid granulomas in many organs, such as the lungs, kidney, skin and eyes [ 50 , 51 ]. Chronic sarcoidosis is disease activity lasting more than 2 years [ 52 , 53 ].…”
Section: Reviewmentioning
confidence: 99%
“… 6 Other studies, such as a retrospective study utilizing the national Veteran Affairs (VA) database, defined eye involvement as orbital granulomas, scleritis and uveitis, and found eye disease in 8.3% of 15,130 patients with a sarcoid diagnosis (via International Classification of Disease codes), a frequency more similar to the one seen in our study. 15 …”
Section: Discussionmentioning
confidence: 99%
“… 7 Similarly, a study of a predominantly black cohort of 63 individuals with biopsy-proven sarcoidosis in Chicago also reported a higher frequency of panuveitis among patients with sarcoid uveitis (42%, 10/24 in whites and 54%, 21/59 in blacks). 10 Other studies, however, such as a prospective study in Minnesota of a predominantly white population, 3 as well as the VA study (50% black), 15 found anterior uveitis to be the most common uveitis sub-type.…”
Section: Discussionmentioning
confidence: 99%
“…7 Similarly, a study of a predominantly black cohort of 63 individuals with biopsy-proven sarcoidosis in Chicago also reported a higher frequency of panuveitis among patients with sarcoid uveitis (42%, 10/24 in whites and 54%, 21/59 in blacks). 10 Other studies, however, such as a prospective study in Minnesota of a predominantly white population, 3 as well as the VA study (50% black), 15 found anterior uveitis to be the most common uveitis sub-type. The second aim of this study was to evaluate risk factors for ocular sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%